Population Pharmacokinetics of Casirivimab and Imdevimab in Pediatric and Adult Non-Infected Individuals, Pediatric and Adult Ambulatory or Hospitalized Patients or Household Contacts of Patients Infected with SARS-COV-2 - Kuan-Ju Lin; Kenneth C. Turner; Maria Rosario; Lutz O. Harnisch; John D. Davis; A. Thomas DiCioccio (Pharmaceutical Research, 2024)
Introduction Casirivimab (CAS) and imdevimab (IMD) are two fully human monoclonal antibodies that bind different epitopes on the receptor binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and block host receptor interactions. CAS + IMD and was developed for the treatment and prevention of SARS-CoV-2 infections. Methods A population pharmacokinetic (PopPK) analysis was conducted using pooled data from 7598 individuals from seven clinical studies to simultaneously fit concentration–time data of CAS and IMD and investigate selected covariates as sources of variability in PK parameters. The dataset comprised CAS + IMD-treated pediatric and adult non-infected individuals, ambulatory or hospitalized patients infected with SARS-CoV-2, or household contacts of patients infected with SARS-CoV-2. Results CAS and IMD concentration–time data were both appropriately described simultaneously by a two-compartment model with first-order absorption following subcutaneous dose administration and first-order elimination. Clearance estimates of CAS and IMD were 0.193 and 0.236 L/day, respectively. Central volume of distribution estimates were 3.92 and 3.82 L, respectively. Among the covariates identified as significant, body weight and serum albumin had the largest impact (20–34%, and ~ 7–31% change in exposures at extremes, respectively), while all other covariates resulted in small differences in exposures. Application of the PopPK model included simulations to support dose recommendations in pediatrics based on comparable exposures of CAS and IMD between different weight groups in pediatrics and adults following weight-based dosing regimens. Conclusions This analysis provided important insights to characterize CAS and IMD PK simultaneously in a diverse patient population and informed pediatric dose selection.